Developing Cultural Competence in Spanish Language Education through Digital Learning Technologies in the Higher Education System of Uzbekistan - Anastasiya Aleksandrovna Tkacheva (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Abstract: The article examines the role of digital learning technologies in developing cultural competence among students studying Spanish in the higher education system of Uzbekistan. The study analyzes modern linguodidactic approaches that emphasize the integration of cultural knowledge with language acquisition. Particular attention is given to the use of multimedia platforms, virtual learning environments, and authentic cultural materials that facilitate students’ understanding of the sociocultural context of Spanish-speaking countries. The research demonstrates that innovative digital tools contribute significantly to the development of intercultural awareness, communicative flexibility, and cultural sensitivity among students learning Spanish as a foreign language.